Living Like A Monk: Motivations and Experiences of International Participants in Templestay - Chun, Byunggil (The international journal of religious tourism and pilgrimage, 2017)
Templestay has transformed the perception and traditional role of Buddhist monasteries into a hybrid form of leisure and recreational dwelling that transcends religious boundaries. We identify four domains of motivational variables including learning, self-growth, being with nature, and relaxation. Based on data from 299 international participants in Templestay, empirical tests of the hypotheses revealed that motivational domains such as self-growth, nature, and learning exhibited significant differences based on the various socio-demographic backgrounds of international participants. Strategies are suggested for crafting Templestay as a cultural and monastic experience as well as segmenting and targeting international participants based on their needs.